Implementation of the Project Based Learning (PjBL) Model to Improve Islamic Religious Education Learning Outcomes for Class XII BDP 3 Students at SMK Negeri 9 Samarinda - Syahamah, Siti (PT Literasi Nusantara Publisher, 2022)
The purpose of this study was to determine the increase in student learning outcomes in Islamic Religious Education (PAI) learning by applying the Project Based Learning (PjBL) learning model which was measured by using an increase in the percentage of students who scored above the KKM (Complete) in each cycle. The research that has been done includes Classroom Action Research (PTK) and data collection techniques using qualitative and quantitative techniques. Existing data, obtained from the results of observations, interviews, documentation and field notes. This research has been done in 2 cycles. The method of measuring learning outcomes is carried out using tests, namely pre-test and post-test which are carried out in each cycle. Based on existing data, there is an increase in the percentage of students who get the predicate complete in each cycle. In the pre-test at the beginning of the first cycle, there were 32.2% of the total number of students who completed the school's KKM scores. At the end of the first cycle, namely the post-test results, there were 35.8% of the total number of students who completed and the post-test results at the end of the second cycle were 92.9% of the number of students in class XII BDP 3 who received the Completed predicate above the KKM score. It can be said that the application of the Project Based Learning (PjBL) learning model can improve student learning outcomes in class XII BDP 3 SMK Negeri 9 Samarinda.